Analisis Faktor Permintaan Properti Residensial 34 Provinsi Indonesia Periode 2019 - 2021 - Wardoyo, Yanuar Akbar (Trunojoyo University of Madura, 2023)
This research aims to determine the influence of property price variables, regional income (GRDP), population and facilities (regional access and infrastructure) on demand for residential property in 34 provinces in Indonesia. This research uses panel data obtained from the websites of the Central Statistics Agency (BPS) and Bank Indonesia (BI). The data in this research consists of property prices, regional income (GRDP), population, facilities (regional access and infrastructure) and the amount of residential property financing realization which is proxied as demand for residential property in 34 provinces in Indonesia in 2019 - 2021 (annual). The statistical model used is multiple linear regression analysis using the F test and t test. The results with the F test show that the independent variables (property prices, regional income (GRDP), population and facilities index) have a significant effect on demand for residential property in 34 provinces in Indonesia. Apart from that, the results of the t test show that the property price and population variables partially have a significant effect on Indonesian property demand, while the regional income (GRDP) and facility index variables do not have a significant effect on Indonesian property demand.